Cross influence of discharge and circulation on head loss of conduit of pump system with low head - 陆伟刚 董雷 王兆飞 陆林广 (Applied mathematics and mechanics, 2012)
The relationship between the head loss and the discharge and circulation of the conduit of a pump system with low head is an important problem with an obvious influence on the improvement of its hydraulic performance. The velocity circulation from the pump guide vane makes the relationship more complicated, which has to be understood comprehensively. The results indicate that, under the condition of zero circulation, the head loss of the inlet and outlet conduits is in proportion to the square of discharge. Under the condition that the Reynolds number is satisfied with the resistant square area, the conduit loss is in proportion to the square of discharge for the similar working points with different speeds in a certain rotational speed range, indicating that the pump system efficiency is constant. The outlet conduit loss of design discharge for a pump system with low head depends on the velocity circulation from the guide vane exit, and the relationship between the loss and the circulation is an open curve with an upward direction, meaning that there is an optimal circulation for the loss. Under the condition of various working points for a pump system with low head, the head loss of the outlet conduit is under the cross influence of both the discharge and the circulation. As a result, the relationship between the head loss and the discharge is almost linear, and the mechanism needs to be further studied.